Electronic structure analysis of the quasi-one-dimensional oxide Sr6Co5O15 within the LDA+U method - Botana, A. S. (2011)
The quasi-one-dimensional cobalt oxide Sr6Co5O15 is studied using first-principles electronic-structure calculations and Boltzmann transport theory. We have been able to describe the electronic structure, characterized by the structural one-dimensionality and a particular type of charge ordering, with unexpected electronic structure of the different Co atoms. The origin of the large unquenched misaligned orbital angular momenta comes out naturally from a correct description of the different crystal-field environments. The evolution with the on-site Coulomb repulsion (U) of the electronic structure and the transport properties is discussed, with a best agreement with experiment found for the smallest value of U that allows to converge the correct in-chain ferrimagnetic ground state.